Mihi cordi (est): Università e “dovere di connessione” - Farinelli, Giovanna (Studi sulla Formazione/Open Journal of Education, 2022)
A reflection also imposes itself on the Italian university "after" the Pandemic. In fact, this contribution represents the unedited elaboration of my brief speech at the Third Brainstorming of the University, Designing the University of the Future (University of Perugia, 29 March 2021). On this occasion, the need to "design the University of the future" with the mind turned to the past, recovering the basic values of the university of the origins (Civitatis Perusii A.D. MCCCVIII), was underlined (Studium Generale, Universitas Studiorum, quaestio quodlibetalis etc.), in order to reaffirm the personalization and quality of the educational relationship through accredited/institutional but direct contacts/profiles (e.g. Microsoft Teams).